Gas exchange in lisianthus plants (Eustoma grandiflorum) submitted to different doses of nitrogen - Marchese, J. A.; Katz, I; Sousa, A. P.; Rodrigues, J. D. (Acad Sci Czech Republic, Inst Experimental Botany, 2005)
The effect of different doses of nitrogen (N) on gas exchange, relative chlorophyll (Chl) amount, and the content of N in the aerial biomass of lisianthus was evaluated. The treatments consisted of six different concentrations of N (50, 100, 150, 200, 250, and 300 g m(-3) noted as N-50, N-100, N-150, N-200, N-250, and N-300, respectively), applied through the fertirrigation technique. N-250 and N-300 induced increase in the contents of foliar Chl and N in the aerial biomass, that in turn contributed to an increase of photosynthetic activity in lisianthus.
Keywords: chlorophyll; mineral nutrition; photosynthesis; stomatal conductance; transpiration